Euthanasia from the Islamic Perspective: Ending Life of a Patient whose Recovery is Absolutely Impossible - U Tun Aung, Maularna Akbar Shah @ (IIUM Medical Journal Malaysia, 2018)
Life and death of men is in the discretion of Allah, SWT. No one can decide how long they should live, but Allah, SWT. However, in our society today, life is being terminated by someone such as doctor or family of terminally ill patients when their recovery is absolutely irretrievable according to medical expert opinions. In medical science, ending life for such a situation is called euthanasia i.e. an act or practice of painlessly putting to death persons suffering from painful and incurable disease or incapacitating physical disorder or allowing them to die by withholding treatment or withdrawing artificial life-support measures. Justification given by pro-euthanasia is that it is the right of the patient who should not suffer unbearable pain physically and who does want to be a burden to their family. They insisted mercy killing is absolutely appropriate if the patient’s body is in gradual decline, their organs are in continuous failure, their agonizing pain is unbearable, and the cost of their artificial support system is beyond their limit. This issue has been controversial to many Islamic as well as social organizations as it is against their doctrine and norms. Since life and death is in Allah’s hand, who is to decide that a life has to be ended at a specific time? Is it against predestination and fixation of life by Allah that when the time come no one can stop its arrival? This undesirable situation is confronted by many Muslims in our world too, hence is there any room in Shari’ah law that allows a physician to end the life of a patient? The objective of this paper is to explore any possibility in Shari’ah law that authenticates ending of a life.